CROSS-CULTURAL AND LINGUISTIC ISSUES IN ADVERTISING TRANSLATION: THE CASE OF UZBEK LANGUAGE - Adinayev Odiljon Jumanazarovich (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
Translating advertisements into Uzbek is a complex process that requires linguistic, cultural, semantic, and pragmatic competence. This paper analyzes the main challenges encountered when translating advertisements and examines strategies for preserving the effectiveness, humor, emotional impact, and persuasive power of the original texts. Special attention is given to linguistic issues such as idiomatic expressions, polysemy, and brevity; cultural factors including humor, social norms, and references; semantic problems involving metaphors, ambiguity, and connotation; and pragmatic aspects such as tone, style, and audience expectations.